Thromboprophylaxis of elderly patients with AF in the UK: an analysis using the General Practice Research Database (GPRD) 2000–2009. Issue 2 (19th October 2012) - Scowcroft, Anna C E; Lee, Sally; Mant, Jonathan
Abstract : Objective: To assess use of thromboprophylaxis in UK general practise among patients with atrial fibrillation (AF); to investigate whether elderly patients are less likely to receive anticoagulation therapy than younger patients. Design: Retrospective cohort study Setting: UK General Practice Research Database (GPRD) Patients: Aged ≥60 years with a new diagnosis of AF (2000–2009). Interventions: None. Main outcome measures: The main outcome measure was initiation of warfarin in the first year following diagnosis. Patients were categorised by stroke risk (CHADS2 score) and bleeding risk (HAS-BLED score). Results: 81 381 patients were identified (21% aged 60–69 years, 37% aged 70–79 years, 42% aged 80+ years). Patients aged 80+ years were significantly less likely to be initiated on warfarin than younger patients, adjusted for gender, practice and comorbidities; 32% of patients aged 80+ years received warfarin compared with 57% aged 60–69 years (p<0.0001), and 55% aged 70–79 years (p<0.0001). For all strata of CHADS2 /HASBLED scores, patients aged 80+ years were significantly less likely to be treated with warfarin than younger patients. Logistic regression showed that female sex, low Basal Metabolic Index (BMI), age over 80 years, increasing HAS-BLED score and dementia were independently associated with reduced use of warfarin. Stroke/Transient Ischaemic Attack (TIA), hypertension, heart failure and left ventricular systolic dysfunction were associated with increased use. Patients with HAS-BLED>CHADS2 were less likely to be initiated on warfarin. Higher CHADS2 scores were associated with increased anticoagulation use. Conclusions: Anticoagulation is being under-used in patients with AF aged 80+ years, even after taking into account increased bleeding risk in this age group.